Geospatial Approach for Coastal Vulnerability Assessment of Selangor Coast, Malaysia. Issue 1 (May 2021) - Mohd, F A; Rahman, A A A; Maulud, K N Abdul; Kamarudin, M K; Majid, N A; Rosli, A
Abstract: The The length of the coast of peninsular Malaysia is approximately 4, 809 km long. Coastal erosion is recognized as the permanent loss of land and habitats along the shoreline resulting in the changes of the coast. Thus, the aim of this study is to determine the vulnerability of erosion of the Selangor coast caused by sea level rise events. In this paper, by using satellite imagery, both manual methods and coastal extraction processing have been examined. Six variables consist of the coastal vulnerability index (CVI), which are coastal geomorphology, coastal slope, erosion and accretion rate, mean wave height, mean tidal range, and the increase in sea level. Vulnerability levels are classified into five vulnerabilities for 8 management units along the Selangor coast which are very medium, medium, moderate, high and very high. The finding reveals that the level of vulnerability of MU 7 Pantai Jeram & Bagan Sungai Janggut is very high because the rate of erosion in the area is higher compared to other areas. Finally, the outcome of this study provides a framework that can be used by decision makers, and relevant authorities to implement mitigation and adaptation measures in the effort to deal with the impacts of climate change on coastal regions.